Analisis Penerapan Good Corporate Governance pada Bank Muamalat KC Bengkulu - Anis Tri Handayani; Eka Sri Wahyuni; Yunida Een Fryanti (UNIVED Press, 2022)
This study aims to determine how the implementation of Good Corporate Governance at Bank Muamalat KC Bengkulu. In good corporate governance (GCG), there are principles that are implemented in the form of general implementation in every Islamic banking in Indonesia. This research was built with the belief that with the implementation of GCG in a company, the company has good management. In this study the authors used a descriptive qualitative approach. Based on the results of this study, it can be concluded that there is an important role between the implementation of GCG and the inhibiting and supporting factors in the implementation of GCG practices, where by applying the principles of GCG in accordance with sharia principles, the implementation of GCG implementation becomes focused and becomes better from year to year so that it becomes a motivation. the company in implementing and understanding GCG in general and based on sharia principles is also very important to be applied to each individual who is responsible for the tasks that have been mandated by Bank Muamalat KC Bengkulu in order to achieve the vision, mission, culture and code of ethics of the company according to Islam, as well as institutions who is supervising.